Nano-FTIR spectroscopy of surface confluent polydopamine films - What is the role of deposition time and substrate material? - Kral, Martin; Dendisova, Marcela; Svoboda, Jan; Cernescu, Adrian; Svecova, Marie; Johnson, C Magnus; Pop-Georgievski, Ognen; Matejka, Pavel (Colloids and surfaces. B, Biointerfaces, 2024)
Polydopamine (PDA) is a widely used anchoring layer for multiple purposes. While simple to prepare, PDA is characterized by high chemical and topological diversity, which can limit its versatility. Unraveling the formation mechanism and physicochemical properties of continuous confluent layer and adherent nanoparticles on the nanoscale is crucial to further extend the prospective applications of PDA. Utilizing nano-FTIR spectroscopy, we investigate layers of PDA on three different substrates (silicon/silicon dioxide, nitrogen-doped titanium oxide, and gold substrates) at varying times of deposition (ToD). We observed a good correlation between the nano-FTIR and macroscopic FTIR spectra that reflected the changes in the relative abundance of PDA and polymerization intermediates as ToD increased. To gain analytical power, we utilized the principal component analysis (PCA) and extracted additional information from the resulting loadings spectral curves and data distribution in the score plots. We revealed a higher variability of the spectra of ultrathin surface confluent layers compared to the adherent nanoparticles. While the spectra of nanoparticles showed no apparent dependency on either ToD or the substrate material, the spectra of layers were highly affected by the increasing ToD and exhibited a rise in the absorption of PDA. Concomitantly, the spectra of layers grouped according to the substrate material at the lowest ToD point to the fact that the substrate material affects the PDA's initial physicochemical structure. The observed separation gradually diminished with the increasing ToD as the PDA physicochemical structure became less influenced by the substrate material.
Keywords: polymery; Nanoparticles; Vibrational nanoscopy; Indoles; Infrared; oxid dusnatý; Polymers; Nano-FTIR; Polydopamine; indoly; spektroskopie infračervená s Fourierovou transformací; Spectroscopy, Fourier Transform Infrared; Anchoring layers; Nitric Oxide; Self-assembly; nanočástice